Imaginary and symbology of water in six classical themed poems by Jorge Luis Borges - Valenciano, Minor Herrera (2020)
The symbolism of water and the imaginary emerged around it constitute one of the literary manifestations most extensively exploited by the Latin American authors of the Boom, because this element weaves a series of intricate relationships in which the metaphysical world joins the physical world; consciousness with the collective unconscious, reason and passion. This article shows how water occupies an essential position in some classic poems (Greco-Latin) written by Jorge Luis Borges to develop ideas such as forgetting, death, time and discontinuity, already present in the Greek and Roman imaginaries (well known by the author), and so recurrent in epics stories. For this purpose, the poems entitled Proteo, Brunanburh, En memoria de Angelica, Al espejo, Efialtes, published in the poetry book entitled La rosa profunda(1975) and Heráclito, published in the collection entitled La Moneda de Hierro(1976), will be analyzed.